Description ou prescription ? Les catégories ethnico-raciales comme outils de construction de la nation. Les recensements au Belize, xixe-xxe siècles - Élisabeth Cunin; Odile Hoffmann (Cahiers des Amériques Latines)
This text presents an analysis of the processes of ethnic-racial classification and categorization of the population of Belize throughout 19th and 20th centuries, based on the censuses and the reports of the government. We are interested not so much in the data as such, as with the categories used for counting the population, seen as indicators of political instruments of construction of a colonial, then a national society. Whereas, at the 19th century, the censuses reflect the various modes of apprehension of the population (transition from slavery to freedom, assertion or negation of ethnic-racial diversity), the administrative reports are based on a demographic and spatial model that seem invariant and stereotyped, and used like a simple political management tool. At the 20th century, we analyze the long and difficult walk towards the independence (1982) and the changes introduced by the new State of Belize into one of the processes of construction of a national identity (categories and methodology of census).